(untitled) (CIPEEX, 2025)
The workshop "Create Your Cash Flow and Manage Your Working Capital," developed in partnership with SEBRAE and part of the National Financial Education Week, aimed to train diverse audiences, including micro-entrepreneurs, aspiring business owners, high school students, and administration academics, in the efficient management of cash flow and working capital. The workshop exceeded expectations, providing essential knowledge and practical experiences that enabled participants to optimize their financial operations, reduce risks, and ensure the continuity of their businesses.